Long‐term clinical safety and efficacy of drug‐coated balloon in the treatment of in‐stent restenosis: A meta‐analysis and systematic review. Issue 2 (12th November 2019) - Xi, Yangbo; Chen, Jiahao; Bi, Yuying; Xie, Shuling; Liao, Tong; Zhang, Yuanchun; Kislauskis, Edward; Wu, Tim; Laham, Roger; Xiao, Jianmin
Abstrct: Objectives: The aim of this study was to evaluate the long‐term clinical safety and efficacy of drug‐coated balloon (DCB) in the treatment of in‐stent restenosis (ISR). Background: There is a long‐term safety issue in peripheral arterial disease patients treated with paclitaxel‐coated balloon, this has also raised concerns on DCB in coronary intervention. Methods: Nine randomized controlled trials (RCTs) and nine observational studies (OSs) were included with a total of 3, 782 patients (1, 827 in the DCB group, 1, 955 in the drug‐eluting stent [DES] group) being analyzed. The primary outcome measure—major adverse cardiovascular events (MACEs), target lesion revascularization (TLR), target vessel revascularization (TVR), myocardial infarction (MI), cardiac death (CD), stent thrombosis (ST), all‐cause death (AD), and coronary angiography outcomes included late lumen loss (LLL), minimum luminal diameter (MLD), diameter stenosis (DS) were analyzed. Results: DCB treatment significantly reduced the LLL (MD: −0.13; [CI −0.23 to −0.03], p = .01). No difference was found for MLD (MD: −0.1; [CI −0.24 to 0.04], p = .17) and DS% (RR = 0.98 [CI 0.80–1.20], p = .86). There was no significant difference in TLR, TVR, MI, CD, ST, AD, and the overall incidence of MACEs between the two groups up to 3 years follow‐up. Subgroup analysis for different type of ISR and DES showed no significant difference in the incidence of endpoints, and there is no difference when considering RCTs or OSs only. Conclusions: The safety and efficacy of the DCB and DES in the treatment of ISR is comparable at up to 3 years follow‐up.